Country’s green brand: the core drivers - Us, Yana; Pimonenko, Tetyana; Lyulyov, Oleksii (<center>Conference Proceedings Determinants Of Regional Development</center>, 2022)
In the view of rushing globalization development dissolving the national and cultural frontiers in favor of global brands, countries face the urgency to design their own unique and positive image on the international stage. A strong country's brand is considered to be one of the triggers for attracting foreign investments and tourists, increasing economic and social prosperity. On the other hand, adverse climate changes raise environmental concerns and require decisive action to mitigate and overcome their consequences. Thus, the global mainstreams are green consciousness, environmental protection, rational energy and natural resources consumption, minimizing the environmental burden from business activity and sustaining the environment for future generations. Therefore, green positioning is a competitive advantage and an essential element of the country's brand that increases its reputation and global engagement. However, the systematization of scientific treatises showed that scholars mainly focus on green brand's investigation at the corporate level, while analysis of green brands at the national level is in the initial stage. This study aims to identify and estimate the main drivers of a country's green brand elements. To achieve the study aim, this research involved data for 28 countries (EU members and Ukraine as a potential candidate for joining the EU) from 2010 to 2020. The data were retrieved from the statistical databases of Eurostat, World Bank Open Data, and OECD.Stat. The empirical study estimates the contribution of the country's green brand factors using the principal component analysis. The estimation procedures employed were the correlation analysis, Kaiser-Meyer-Olkin Test, Bartlett's Test of Sphericity and the orthogonal Varimax rotation. All calculations were conducted using the SPSS software tools. The obtained results showed that the factors most contributing to a country's green brand are the export of goods and services, real GDP per capita, secure Internet servers, renewable energy consumption, forest and organic agricultural land. The findings could improve the strategy for promoting a country's green brand and determining its position in the world.